The Influence of Discipline Factors, Work Culture, and Motivation on the Performance of Teachers in State Vocational Schools in Malang City - Gayuh Drianto,; Fajar Supanto,; Yarnest, (International Journal of Research in Social Science and Humanities (IJRSS) ISSN:2582-6220, DOI: 10.47505/IJRSS, 2022)
This study aims to describe the variables of Performance, Discipline, work culture and motivation,and to analyze the significant influence of discipline factors, work culture, and motivation simultaneously on teacher performance. The results of the analysis show that the factors of discipline, work culture and motivation simultaneously affect the teacher's performance. Discipline affects teacher performance, work culture affects teacher performance. Motivation has an effect on teacher performance. Discipline has a dominant effect on teacher performance.